1980
DOI: 10.1007/bf00588688
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hypothermia on the occurrence of the calcium paradox

Abstract: Reperfusion of isolated rat hearts with Ca2+-containing medium, after a short Ca2+-free perfusion period, results in irreversible cell damage (calcium paradox). In this investigation the effect of hypothermia during (a) the Ca2+-free perfusion period and (b) the phase of reperfusion with Ca2+-containing medium was studied. Failure of the heart to recover mechanical activity, and creatine kinase release were used to define cell damage. Ca2+-free perfusion was performed at 37 degrees, 30 degrees, 25 degrees and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

1981
1981
2002
2002

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 17 publications
2
12
1
Order By: Relevance
“…Whereas we used intact adult rat hearts at 37°C, Goshima et al (1980) used isolated myocytes prepared from fetal mouse hearts, and they carried out their experiments at 25°C. The Ca ++ paradox is age-(Chizzonite and Zak, 1981;Frank and Rich, 1983) and temperature-sensitive (Holland and Olson, 1975;Alto and Dhalla, 1979;Boink et al, 1980;Langer, 1982, Baker et al, 1983). The use of isolated myocytes must also be taken into account, because some of the damage that occurs upon repletion results in physical disruption of the weakened intercalated discs, an event which will create abnormal routes of Ca ++ entry (Ganote et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas we used intact adult rat hearts at 37°C, Goshima et al (1980) used isolated myocytes prepared from fetal mouse hearts, and they carried out their experiments at 25°C. The Ca ++ paradox is age-(Chizzonite and Zak, 1981;Frank and Rich, 1983) and temperature-sensitive (Holland and Olson, 1975;Alto and Dhalla, 1979;Boink et al, 1980;Langer, 1982, Baker et al, 1983). The use of isolated myocytes must also be taken into account, because some of the damage that occurs upon repletion results in physical disruption of the weakened intercalated discs, an event which will create abnormal routes of Ca ++ entry (Ganote et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Mansier and Lelievre (1982) perfused rat heart for 1 minute at room temperature with Ca ++ -free buffer and demonstrated a conversion of heart Na + ,K + -ATPase into a form highly sensitive to ouabain. Although other laboratories have shown that hypothermic Ca ++ -free perfusion does not lead to a complete Ca ++ paradox (Holland and Olson, 1975;Boink et al, 1980;Rich and Langer, 1982), the observation of Mansier and Lelievre (1982) indicates that the operation of Na The depression of Na + ,K + -ATPase after Ca ++ depletion cannot be attributed to gross changes in the protein pattern of SL membranes. It is important to emphasize here that the employed SDS-PAGE separation technique detects changes only in the molecular weight of SDS-denatured proteins.…”
Section: Sl Function After Ca ++ Depletionmentioning
confidence: 95%
“…The dependence of a calcium paradox induction on the perfusion temperature and the time of calcium depletion had been previously described by several investigators in the heart of both mammals and ectotherms [12,20]. It has been reported that depriving rat hearts of calcium for periods longer than 10 min predisposes them to the calcium paradox, even when the perfusion temperature is 20°C [12], whereas in the frog heart the induction of this phenomenon depends on the temperature (37°C) and the duration of calcium deprivation (30 min) [20].…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that the induction of the calcium paradox in rat depends on the perfusion temperature and the duration of calcium depletion [12][13]. This phenomenon has been studied in the heart of various other mammalian species than rat such as dog, cat, rabbit, guinea pig, and mouse [10,[14][15] as well as in isolated cardiac myocytes of neonatal mouse, adult rat and in human myocardial strips [16][17].…”
Section: Introductionmentioning
confidence: 99%